IDENTIFIKASI GANGGUAN BELAJAR ANAK USIA KELAS BAWAH SEKOLAH DASAR - Minsih (Jurnal Pendidikan Dasar Flobamorata, 2023)
The aim of this research is to describe the problem of learning disorders in children in the lower grades of elementary school and identify the learning and communication behavior of these children. The research method used is qualitative research with teachers, school principals, and parents as primary and secondary informants. Data collection through interviews observations and documentation studies. The validity of the data used is a triangulation of sources and techniques and data analysis techniques using interactive qualitative data analysis using the Cresswel model, which uses reduction, display, and verification stages. The results of this study show that lower-class children's learning disorders consist of difficulty reading and barriers to children's verbal communication. This problem was experienced by five lower-class students (grades 1 and 2 of elementary school). The learning disorders experienced by Ss, Dd, Gg, DBP, and DLS children vary in the form of difficulties and obstacles in the form of difficulty reading, barriers to verbal communication, and impaired concentration. Based on the results of identification through interviews and observations, the behavior shown by the object of this research is difficulty communicating verbally during presentations, difficulty expressing opinions, difficulty reading discussion results, difficulty working in groups because they have not been able to complete their part of the assignment and difficulty understanding teacher instructions regarding technical work. group. Based on documentation studies, it shows that the learning outcomes of the five children have poor grades in Indonesian and Natural Sciences subjects.